(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Improving diagnostics in healthcare through machine learning (ML) and deep learning (DL) models has shown significant promise in enhancing accuracy, accessibility, and efficiency. These technologies facilitate early disease detection and personalized treatment, ultimately leading to better patient outcomes. The following sections outline key aspects of this transformative impact.